2016
DOI: 10.1021/acs.joc.6b01528
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Substituted 3(2H)-Furanones Using Alkylative Intramolecular Cyclization of Sulfonium Salts

Abstract: The facile alkylative intramolecular cyclization of 3-alkoxycarbonyl-2-oxopropyldiphenylsulfonium salts is described. This simple method can be readily applied to the synthesis of a novel family of 4-alkylated 3(2H)-furanones in moderate to high yields under mild conditions via a one-pot process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…[71] Alternatively,a lkylative intramolecular cyclisation of 3-alkoxycarbonyl-2-oxopropyldiphenylsulfonium salts affords 4-alkylated 3(2H)-furanones in good yields (Scheme7b). [72]…”
Section: Synthetic Routes To Furanone Derivativesmentioning
confidence: 99%
“…[71] Alternatively,a lkylative intramolecular cyclisation of 3-alkoxycarbonyl-2-oxopropyldiphenylsulfonium salts affords 4-alkylated 3(2H)-furanones in good yields (Scheme7b). [72]…”
Section: Synthetic Routes To Furanone Derivativesmentioning
confidence: 99%
“…21b When ethyl 4-chloroacetoacetate ( 34a ) and ethyl 4-bromoacetoacetate ( 34b ) were subjected to the optimal conditions, 35a was observed as a minor product and the dimerization product 36 was the major product (Scheme 8a ). 21a These results indicated that a bulky diphenylsulfonio group was very important for the cyclization as substrates bearing smaller leaving groups (e.g., Cl, Br) underwent intermolecular S N 2 reactions. This strategy also enabled a one-pot preparation of 5-alkoxy-4-alkylfuran-3(2 H )-ones 41 from sulfoniums 37 via alkylation with alkyl halides followed by intramolecular cyclization, showing a wide substrate scope and good functional group tolerance (Schemes 8b and 8c).…”
Section: Electrophilic Alkylation Using Alkylsulfonium Saltsmentioning
confidence: 95%
“…In 2016, Kawano and co-workers disclosed the synthesis of 5-alkoxyfuran-3(2 H )-ones 35 from the intramolecular cyclization of 3-(alkoxycarbonyl)-2-oxopropyl(diphenyl)sulfonium salts 37 in the presence of t -BuOK (Scheme 8a ). 21a Similarly, intramolecular cyclization of (4-aryl-2,4-dioxobutyl)methylphenylsulfonium salts 39 derived from 1-arylethanone 38 produced a family of 5-arylfuran-3(2 H )-ones 40 in excellent yields under ambient conditions (Scheme 8a ). 21b When ethyl 4-chloroacetoacetate ( 34a ) and ethyl 4-bromoacetoacetate ( 34b ) were subjected to the optimal conditions, 35a was observed as a minor product and the dimerization product 36 was the major product (Scheme 8a ).…”
Section: Electrophilic Alkylation Using Alkylsulfonium Saltsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, the group of Kawano described an intramolecular cyclization of 3‐alkoxycarbonyl‐2‐oxopropyldiphenyl sulfonium salts towards 5‐substituted‐3(2 H )‐furanones (Scheme 12). [ 16 ] Different sulfonium salts 53 were prepared by treating various substituted 4‐bromo‐acetoacetates with diphenyl sulfide in the presence of AgBF 4 . These sulfonium salts were then allowed to undergo intramolecular cyclization in the presence of a base.…”
Section: Methods For the Synthesis Of 5‐substituted‐3(2h)‐furanonesmentioning
confidence: 99%